2016
DOI: 10.1016/j.tcb.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine Signaling and Quorum Sensing: Extreme Ends of a Common Spectrum

Abstract: 'Secrete-and-sense cells' can communicate by secreting a signaling molecule while also producing a receptor that detects the molecule. The cell can potentially 'talk' to itself ('self-communication') or talk to neighboring cells with the same receptor ('neighbor communication'). The predominant forms of secrete-and-sense cells are self-communicating 'autocrine cells', which are largely found in animals, and neighbor-communicating 'quorum sensing cells', which are mostly associated with bacteria. While assumed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 72 publications
0
84
0
Order By: Relevance
“…These can include resistance to signals that inhibit cell multiplication [14], growth factor independence [5, 6], a decrease in programmed cell death [79], self-signaling to stimulate cell multiplication [1013], invasiveness and metastasis [14], tumorigenesis in animal models [1517], and a number of additional characteristics [1, 2]. Recently, we demonstrated that tumorigenic cell lines derived from breast tumors, but not non-tumorigenic cell lines, also possess the capacity to generate large cell aggregates in a 3D Matrigel model through coalescence of clonal aggregates formed through the multiplication of single cells seeded in the gel [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…These can include resistance to signals that inhibit cell multiplication [14], growth factor independence [5, 6], a decrease in programmed cell death [79], self-signaling to stimulate cell multiplication [1013], invasiveness and metastasis [14], tumorigenesis in animal models [1517], and a number of additional characteristics [1, 2]. Recently, we demonstrated that tumorigenic cell lines derived from breast tumors, but not non-tumorigenic cell lines, also possess the capacity to generate large cell aggregates in a 3D Matrigel model through coalescence of clonal aggregates formed through the multiplication of single cells seeded in the gel [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Cell-cell communication in multi-cellular organism can be mediated by autocrine signaling, paracrine signaling and juxtacrine signaling (contact-mediated signaling). There is a fundamental trade-off between autocrine and paracrine signaling 28 . The former enables a single cell to talk to itself whereas the latter is designed to allow multiple cell types to talk to each other.…”
Section: Crosstalk Score Of a Ligand-receptor Pair Between Two Cell Tmentioning
confidence: 99%
“…Other environmental factors such as pH, oxygen, phosphate and diffusibility of the growth medium also influence competence development (Chen and Morrison, 1987;Claverys et al, 2002;Echenique et al, 2000;Yang et al, 2010). Thus, the initiation of competence can be considered as a combination of diffusion sensing and autocrine-like signaling (Doğaner et al, 2016;Moreno-Gámez et al, 2017). The competent state is activated in response to several antibiotics, which thereby allow the bacterium to take up foreign DNA and potentially acquire antimicrobial resistance determinants (Prudhomme et al, 2006;Slager et al, 2014;Stevens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%